pada Penyuluhan Edukasi Pentingnya Menjaga Kesehatan Gigi pada Siswa Kelas 4-6 SDN 6 Babakan Madang, Bogor, Jawa Barat - Octavia, Mora; Gaverio, Nicholas Francisco; Hananta, Linawati (Jurnal SOLMA, 2025)
Background: Limited access to health facilities, economic factors, and limited knowledge and insight regarding the importance of maintaining dental health are risk factors for the high incidence of dental and oral problems, especially in children and rural environments. Based on data from Riset Kesehatan Dasar (Riskesdas), dental and oral health problems are most often found in children aged 5-9 years, with a percentage reaching 67%. Dental disease in children not only causes pain but also impacts their self-confidence, cognitive development, and daily activities. One of the villages with a high incidence of dental disease is Babakan Madang Village, Bogor, West Java. There is a need for education about dental health to increase children's awareness and reduce the incidence of dental disease. Methods: The implementation of educational activities regarding dental health began with a pre-test, presentation of material, and a question and answer session, followed by a demonstration of proper steps for brushing teeth, showing an educational video, pre-test, and post-test exercise, and ending with giving goodie bags. Results: There is a significant increase in knowledge and insight regarding dental health, as evidenced by an average score from pre-test to post-test of 16.67%. Conclusion: This educational outreach activity about dental health can increase students' understanding and awareness of dental health in grades 4, 5, and 6 at SDN 6 Babakan Madang about dental health and enable them to apply appropriate steps for brushing teeth. Keywords: Caries; Dental Health Education; Elementary School children; Rural community